TOWARD A NEW PARADIGM OF ORGANIZATIONAL STRUCTURES IN THE AGE OF ARTIFICIAL INTELLIGENCE: A COMPARATIVE THEORETICAL STUDY - Masoud Lajevardi; Mega Arum; Yanti Susanti; Dwi Saleha; Eko Sudarmanto (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This paper aims to develop a novel theoretical framework for organizational structures in the era of artificial intelligence (AI). It conducts a comparative analysis of traditional, modern, and postmodern organizational structures to identify limitations in accommodating AI’s autonomous capabilities. Through extensive literature review and critical analysis, the study synthesizes organizational theories with emerging AI research to propose a new paradigm integrating AI as an active participant in organizational dynamics. The findings reveal a significant theoretical gap in existing models, which predominantly treat AI as a tool rather than an autonomous agent. The proposed AI-driven paradigm emphasizes distributed intelligence, adaptive structural fluidity, human-AI symbiosis, and transparent accountability. The conceptual nature of the study calls for empirical validation across different industries and cultures. The paradigm provides a framework for managers and practitioners to redesign organizational architectures, fostering agility and ethical governance in AI-augmented environments. This research fills a critical gap in organizational theory by positioning AI as a core actor influencing structure and decision-making, offering a comprehensive model for organizations navigating the complexity of the digital age.